Disuse Osteopenia Development with Non Weight-Bearing in Lower Extremity Trauma: CT Hounsfield-Unit-Based Analysis. Issue 1 (January 2022) - Walton, David M.; Farrar, Nicholas; Eichman, Jack; Fuster, Francisco J.; Perdue, Aaron; Hake, Mark; Ahn, Jaimo
Category: Trauma; Other Introduction/Purpose: Disuse osteopenia develops in individuals with decrease lower limb use especially after injury necessitating non-weightbearing, hospitalization or both. However, the nature of this change is not well characterized and, therefore, cannot be appropriately addressed. Conventional CT produces a reliable evaluation of bone quality as Hounsfield Units (HU) and offers the opportunity to longitudinally study bone density in activity-altered patients. The purpose of this study is to estimate the degree of osteopenia in non-weightbearing hospitalized patients and to identify patient-related factors associated with this loss. Methods: Initial screening criteria included patients who presented to the emergency department between January 1, 2010 to August 1, 2020; baseline lower extremity orthopaedic trauma evaluated by CT. Further criteria included CT imaging capturing the ipsilateral hip at the time of admission; a second CT scan, for any indication (eg, small bowel obstruction, diverticulitis, etc) that include that same hip; strict non-weightbearing in between scans. Exclusion criteria included change in weightbearing status and CT imaging changes that would not allow eBMD analysis (eg, intervention). Estimated BMD (eBMD) was measured at baseline and and at the secondary time point via HU approximation 12mm inferior to superior aspect of femoral neck on axial CT. The change in eBMD was calculated as a proxy for disuse osteopenia and the relationship between relative bone loss (as a nominal rate of osteopenia, eBMD loss/time) and patient-specific factors was explored. Results: Of 200, 000 patients who received CT evaluation including their hip during the targeted timeframe, seventeen patients met our inclusion and exclusion criteria. There was an average of 7.3 days (median = 6 days; mode = 4 days; interquartile range: 4 - 8.5 days) between CT scans. The average rate of disuse osteopenia in the cohort was a net average decrease of 7.5 +- 5.8 HU/day. To place in a standardized clinical context, this change is estimated to correlate linearly with respect to change in DEXA BMD T-Score and may be clinically relevant when HU approach values <100. Associated patient factors that may further precipitate osteopenia whilst non-weightbearing are smoking, female gender, and diabetes. Conclusion: We report novel, preliminary data estimating the rate of disuse osteopenia in admitted, non-weightbearing orthopaedic trauma patients. This data underscores an important consideration all physicians should make when non- weightbearing status is being considered or required after injury or admission.